CO2erosion of BaCo0.85Bi0.05Zr0.1O3-dperovskite membranes under oxygen permeating conditions - Song, J.; Qiu, Z.; Gao, J.; Tan, X.; Sunarso, J.; Wang, Shaobin; Liu, Shaomin (Pergamon Press, 2018)
© 2018 Elsevier B.V. CO2-resistant oxygen selective ceramic membranes have wide applications in clean energy delivery and green chemical synthesis. In this work, CO2erosion and O2permeation behavior of BaCo0.85Bi0.05Zr0.1O3-d(BCBZ) perovskite hollow fibre membranes are investigated. The BCBZ hollow fibre was fabricated by a combined phase-inversion and sintering technique. Experimental results indicate that the O2permeation flux can reach 3.07 mL cm-2min-1at 1000 °C under the air/Ar gradient whereas the O2flux reduced significantly in CO2presence depending on the CO2concentration in the feed gas or sweep gas. The deteriorating effect of CO2on the membrane performance in the feed side was more significant than when it was present in the permeate side. One of the BCBZ hollow fibre samples had been tested for more than 190 h; undergoing six thermal cycles from 700 to 1000 °C in different CO2-containing gas streams. With high CO2concentrations up to 10 vol.% in both feed and permeate sides, no permeation was observed due to the strong CO2adsorption on the membrane surface; however, the O2flux can be completely recovered once the CO2became absent in the gas atmosphere. When the membrane test was continued up to 180 h, the O2flux value cannot be fully recovered and 9.6% of the original flux value was lost due to the carbonate salt formation. To get the quantitative information on the erosion rate, more membrane samples had been tested from 1 to -8 days in 10 vol.% CO2at 900 °C under the oxygen permeating conditions. We found that the erosion rate was relatively fast at the beginning stage with corrosion depth up to 3 µm for the first 3 days but slowed down to 1 µm depth for the subsequent 5 days. The significantly reduced erosion rate is due to the higher O2concentration in the locally uncontaminated membrane area (without the carbonate deposition). Inspired by such findings, one future strategy to protect the membrane is to deposit the membrane surface using more robust ion-conducting layer like Sm0.2Ce0.8O1.9.